'In the eyes of the beholder': the influence of academic performance and extracurricular activities on the perceived employability of Chinese business graduates. (24th August 2018) - Pinto, Luísa H; He, Kena
Abstract : We examine whether the academic performance and the participation in extracurricular activities (ECAs) affect the perceived employability of Chinese business graduates by employing an experimental between‐subjects factorial design. Three hundred and sixty Chinese working adults rated the employability of eight fictitious résumés of business graduates from the Peking University, varying in academic performance, participation in ECAs and gender. The results showed that the participation in ECAs, alone and combined with academic performance, resulted in higher rates of job suitability and employability skills. Moreover, the findings revealed an outgroup favouritism towards the applicants with high academic performance and participation in ECAs. These findings are relevant for employers, higher education institutions and graduates because an increasing number of new entrants are seeking to distinguish themselves in the transition to the labour market. Abstract : Key points Three hundred and sixty Chinese working adults rated the employability of eight fictitious résumés. Academic performance (GPA) alone is not enough to boost employability. Extracurricular activities (ECAs) are key to raise business graduates' employability. ECAs and GPA combined foster business graduates' employability. Graduates perceived employability are related to ratters' biographical characteristics which bound their employment prospects.